A descriptive Analysis of Anglicisms used in Ecuadorian Magazines. - Merchán Tamariz, Ana María (2011)
This is an investigation with a qualitative and quantitative approach, carried out in Quito, Ecuador, from April 2010 to March 2011, to determine the linguistic phenomenon of anglicisms used in Ecuadorian magazines. For this purpose, ten different magazines edited and published in Ecuador between 2009 and 2010 were used in order to collect the data collection, three different variables which included cultural, scholarly, and general interest magazines, the ones that better represented all types of the Ecuadorian population were chosen. The data was analyzed in-depth linguistically and comparatively, to determine the semantics, syntax, pragmatics, and morphological aspects of the English words incorporated into the lexicon of the Spanish language.